Racial Alterity, Wixarika Youth Activism, and the Right to the Mexican City - Negrín, Diana (The University of Arizona Press, 2019)
"Utilizing archival and ethnographic research, this book explores the construction of racial and ethnic imaginaries in the western Mexican cities of Guadalajara and Tepic, and the ways in which these imaginaries shape the contemporary experiences and activism of Wixarika (Huichol) Indigenous university students and professionals living, studying, and working in these two cities"--